Comparative study of root anatomical character of Ficus carica L. between different planting medium - Rusmadi, Nadira Nazua; Che Amri, Che Nurul Aini; Shahari, Rozilawati; Tajudin, Nur Shuhada; Mispan, Mohd Razali (2017)
Ficus carica L. (Fig) are known as one of the medicinal plants that harvested worldwide for its dry and fresh consumption. Its different parts such as leaves, stem, barks, fruits and roots are used in traditional medicine from ancient age to treat various disease. This research was conducted to study the effect of different planting medium to the root anatomy of Brown Tukey Masui (BTM6) fig varieties. The fresh primary, secondary, and tertiary root of BTM6 varieties were soaked into the AA solution (acetic acid: 70% alcohol) with 1:3 ratio. Then, it was cut in cross section before undergo processor, embedding and sectioning process. After staining, the root anatomical observation was performed by using light microscopic LeicaTM brand. As a result, root anatomical characteristics for species studied were described. The observations were made on arrangement of rays, vessel elements, axial parenchyma, fibres, diameter of roots and cortex using Las EZ software. Cross section of primary and secondary roots of the studied species showed slightly variation. While the tertiary roots observation revealed more differences in the anatomical character especially in diameter of roots by using Las EZ software. In conclusion, different media give some effect to the growth and characteristics of root anatomy for BTM6 varieties.